Catalytic air pollution control - Heck, Ronald M. (Van Nostrand Reinhold, 1994)
The first five chapters describe the fundamentals of catalysts and catalysis. Two new chapters have been added on the chemical and physical properties of monoliths, the support of choice for environmental applications. Included are chapters on fuel cells/ fuel processing and novel approaches for purifying ambient air.